Peran guru dalam menanamkan nilai-nilai keislaman melalui pesantren-based curriculum (PBC) di madrasah aliyah - Mashudi, Alfi; Rizal, Syaiful (Al-Liqo: Jurnal Pendidikan Islam, 2025)
Islamic education plays a strategic role in shaping the character and morals of students. One relevant approach is the Pesantren-Based Curriculum (PBC), which adopts the pesantren education method in madrasahs. This study examines the role of teachers in instilling Islamic values ​​through PBC at MA Al Huda Kotawaringin Lama, as well as the challenges in its implementation. Using a qualitative case study method, the results of the study show that teachers play a central role as educators, facilitators, and role models through learning yellow books, habituating worship, and instilling morals. The obstacles faced include limited facilities, lack of teacher understanding of PBC, and challenges of integration with the formal curriculum. Globalization and technology demand innovation in learning. The success of PBC is determined by teacher competence, role models, and institutional support. Strengthening teacher capacity and supporting policies are strategic steps to optimize the role of teachers in shaping a generation of Muslims with character.